Pengaruh Penggunaan Terapi Adjuvant Terhadap Kesembuhan Pasien Covid 19 : Studi Literature - Marlin Sutrisna (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Adjuvant therapy is now a trend issue in the world and in Indonesia in the face of the COVID-19 pandemic. The purpose of this paper is to examine the literature on the effect of using adjuvant therapy on covid 19 patients. This literature review uses e-database sources: ebscohost, proquest, pubmed, and science direct, where the articles used in 2015-2021 with keywords adjuvant therapy and covid 19. There were 7 articles that met the inclusion criteria. The entire article states that adjuvant therapy provides benefits for healing covid 19 patients. Research that has had a clinical improvement effect on covid 19 patients conducted by Chavarria (2020) uses antioxidants and pentoxifylline. Shohan et al, (2021) used quercetin in combination with antiviral drugs. Castillo et al, (2020) use melatonin. Trejo et al, (2021) used hydrogen peroxide. Luo et al, (2020) use of traditional Chinese medicine. Jamali MoghadamSiah et al, (2021) used high doses of vitamin C and Hiedra et al (2020) used intravenous vitamin C. The key to adjuvant therapy is vitamin C, Chinese medicine, hydrogen peroxide, antioxidants and pentoxifylline, melatonin and quercetin, which can be used as adjuvant therapy for healing and clinical improvement in COVID-19 patients.